Letter (copy) : Foodstuffs for Spain - Tewson, Vincent
030-0214-001 EXPORT ST/HP.345.HVT/FC/EK/510. Secretary's. 2nd February, 1938. Mr. E. Winstanley, Export Department, Co-operative Wholesale Society Limited, 1, Balloon Street, MANCHESTER, 4. Dear Mr. Winstanley, FOODSTUFFS FOR SPAIN. Referring to your letter of the 31st January, I think your explanation clears up the question of demurrage charges in connection with goods shipped on the s.s. HARTBRIDGE. Accordingly I am enclosing a cheque for £37.12.4. in settlement of the charges for which I shall be glad to have your receipt in due course. Yours sincerely, Assistant Secretary. Cheque. 292/946/30/214